1999
DOI: 10.1164/ajrccm.159.3.9607099
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Factors for the Development of Bronchiolitis Obliterans Syndrome

Abstract: Chronic rejection after lung transplantation, manifesting as bronchiolitis obliterans syndrome (BOS), has become the dominant challenge to long-term patient and graft survival. In order to elucidate risk factors for development of BOS we utilized the 1995 revision of the working formulation for the classification of lung allograft rejection (), and devised a quantitative method to retrospectively study lung transplant biopsies from all patients who survived at least 90 d. All transbronchial biopsies were regra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
170
0
7

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(180 citation statements)
references
References 12 publications
3
170
0
7
Order By: Relevance
“…Immunologic factors suggested to have a role in the development of BOS include acute rejection, 25,26 lymphocytic bronchitis, 27,28 HLA mismatch [29][30][31] and CMV pneumonitis, 8,[32][33][34] and non-immunologic factors include ischemia, 30 donor age 35 and recipient age. 36 In the present study we found that infections, an indication for transplant of emphysema, and female recipient status were also independent predictors of earlier development of BOS2, whereas female recipient status was associated with earlier onset of BOS3.…”
Section: Discussionmentioning
confidence: 99%
“…Immunologic factors suggested to have a role in the development of BOS include acute rejection, 25,26 lymphocytic bronchitis, 27,28 HLA mismatch [29][30][31] and CMV pneumonitis, 8,[32][33][34] and non-immunologic factors include ischemia, 30 donor age 35 and recipient age. 36 In the present study we found that infections, an indication for transplant of emphysema, and female recipient status were also independent predictors of earlier development of BOS2, whereas female recipient status was associated with earlier onset of BOS3.…”
Section: Discussionmentioning
confidence: 99%
“…confirmaram 19 casos pediátricos, após revisarem todos os casos de autópsia (n = 2.897) e biópsia pulmonar (n = 244) realizadas no Hospital Infantil Saint Christopher, na Filadélfia, durante um período de 25 anos 9 . No entanto, nas últimas décadas, surgiu um interesse crescente a respeito dessa doença em adultos (Figura 1), devido ao reconhecimento de novos fatores causais, principalmente transplante de órgãos [10][11][12][13][14][15][16] .…”
Section: Introductionunclassified
“…confirmaram 19 casos pediátricos, após revisarem todos os casos de autópsia (n = 2.897) e biópsia pulmonar (n = 244) realizadas no Hospital Infantil Saint Christopher, na Filadélfia, durante um período de 25 anos 9 . No entanto, nas últimas décadas, surgiu um interesse crescente a respeito dessa doença em adultos (Figura 1), devido ao reconhecimento de novos fatores causais, principalmente transplante de órgãos [10][11][12][13][14][15][16] .Em crianças, na maioria das vezes, a BO é precedida por uma infecção das vias aéreas inferiores, principalmente causada por adenovírus [17][18][19][20][21] . Em contraste com o número crescente de referências bibliográficas sobre a BO em adultos, essa doença ainda não chamou a atenção dos pediatras.…”
unclassified
“…This process results in receptor activation (Costantino et al 1999;Rondard and Pin 2015;Takahashi et al 1993). The other binding site, for positive and negative allosteric modulators, is located within the 7TM domain (Carroll et al 2001;Gregory and Conn 2015;Litschig et al 1999). Binding of a negative allosteric modulator to this site results in non-competitive inhibition of the receptor.…”
Section: Pharmacologymentioning
confidence: 99%
“…MCPG is non-selective (Hayashi et al 1994), AIDA is selective for mGlu 1 over mGlu 5 (Moroni et al 1997), and LY367385 is selective for mGlu 1 (Clark et al 1997). Selective non-competitive inhibitors (negative allosteric modulators) include CPCCOEt for mGlu 1 (Litschig et al 1999) and MPEP and MTEP for mGlu 5 (Brodkin et al 2002;Gasparini et al 1999;Lea and Faden 2006).…”
Section: Pharmacologymentioning
confidence: 99%